Perfil alimentar e nutricional de pré-escolares de uma creche institucional da cidade de Santa Maria - RS - Valente, Tessa Bitencourt (2009)
It is critical to adequate food since childhood, mainly due, growth and intellectual development. Is the preschool age eating habits are formed and passed on to the nutritional status of children. This study aimed to analyze the food intake and nutritional status of preschool children in a day care center, through the weighed food record served in the institution with subsequent chemical analysis; 24-hour food recall was performed complemented by the food intake of the child at home; a food frequency questionnaire; and growth curves proposed by the World Heath Organization. Dietary reference intakes were used to assess the adequacy of dietary intake of children. It was found inadequate food intake at daycare center, with high percentages of carbohydrates, lipids and proteins in the lower limit to the recommendation. The consumption at home was characterized by an energy and protein intake excessive. Analyzing the total daily intake of children, the average intake of protein and carbohydrates were higher than the recommendation, and lipids remained within the proper range. The percentage of inadequate energy was 92.31%; iron 46.15%; carbohydrates 10.25%; phosphorus and zinc 5.13%; magnesium 2.56%. There was no presence of nutritional deficits and most children were well-nourished. The data show a high prevalence of inadequate energy, some minerals and fiber, and a tendency to overweight. Therefore, there is need for a revision and adaptation of the menus of the institution to better meet the needs of preschoolers; and nutritional guidance to parents so that does not a super feeding at home in order to avoid excessive weight gain in childhood with the associated consequences for health.